Swamp spook : a [Miss Fortune Mystery, Book 13] - DeLeon, Jana (DeLeon, Jana. Miss Fortune series., 2018)
"When black cats roam, and spooks are seen, Come celebrate, it's Halloween. Sinful, Louisiana, really knows how to throw a party, and it goes all out for Halloween. The weeklong celebration kicks off with a maze of horror in the park built of hay bales. And Fortune has the perfect assignment -- the executioner. Her scene comes complete with a head block, a hatchet, and a fake body with removable head. It's the perfect setup ... for a crime. When Fortune returns from break and realizes the body in her scene is a real one and not the prop, she knows trouble is coming. Before she can shake a broomstick, Celia Arceneaux has raised the alarm and the state police show up to take over the investigation. With Carter on the sidelines and Fortune the prime suspect, Swamp Team 3 sets out to catch a real monster."--Amazon.